Weak Solutions for a p-Laplacian Antiperiodic Boundary Value Problem with Impulsive Effects - Keyu Zhang; Jiafa Xu; Wei Dong (Discrete Dynamics in Nature and Society)
By virtue of variational method and critical point theory, we will investigate the existence of weak solutions for a p-Laplacian impulsive differential equation with antiperiodic boundary conditions.